NIAT MELAKUKAN WHISTLEBLOWING: PERSEPSI MAHASISWA DIPLOMA III EKONOMI - Afuan Fajrian Putra; Yestias Maharani (Jurnal Akuntansi Indonesia, 2018)
This study aims to examine the factors that can affect the economics student intention of doing whistleblowing. The variables used in this study refer to the Theory of Planned Behavior is the attitude towards behavior, subjective norms, and perceived behavioral control which will then be tested for its effect on the intention to do whistleblowing. This study will examine these factors partially and simultaneously. This study uses a population of all active diploma 3 economics students in one of the private universities in Yogyakarta. While the number of samples used in this study using the Slovin Formula as many as 88 respondents. Data collection techniques in this study using a questionnaire with data analysis methods and tools using multiple regression analysis using SPSS version 16. The results of this study indicate that the variable attitudes toward behavior and subjective norm partially positive influence on the intention of doing whistleblowing. While perceived behavior control variables do not have a positive effect on the intention to do whistleblowing. Simultaneously variable attitudes toward the behavior, subjective norms, and perceived behavioral control significantly influence the intention of doing whistleblowing.Keywords: Attitude, Subjective Norm, Perceived Behavioral Control, Theory of Planned Behavior, Intention